Speech Acts in Strategic Diplomacy: An Analysis of Joe Biden’s Address on the Israel–Hamas Conflict - Degaf, Agwin; Hidayah, Rofiatul; Anggrisia, Nur Fitria; Setyawan, Agustinus Hary (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
Political speeches influence the formation of public opinion, the construction of ideological narratives, and the direction of international diplomacy. This study aims to identify and analyze the illocutionary acts in U.S. President Joe Biden’s Oval Office address on the Israel–Hamas conflict and to examine how language is used to articulate political stance and strategic diplomatic positioning. Using Searle’s typology of assertive, directive, commissive, expressive, and declarative acts, this research employs a descriptive qualitative method based on the official transcript published by The New York Times and the corresponding video released by Sky News. The findings show that assertive acts dominate the speech, functioning to reinforce factual claims, establish credibility, and clarify the United States’ foreign policy orientation. Commissive and expressive acts appear frequently to project moral commitment, empathy, and alignment with selected stakeholders, while directive and declarative acts are used sparingly to encourage support without demanding immediate action. These results indicate that Biden’s speech employs speech acts strategically to balance assertive leadership with humanitarian rhetoric in a high-stakes diplomatic context. The study contributes to pragmatic research on political discourse by demonstrating how speech acts operate as strategic tools for managing international crises. Future research may extend this analysis by examining audience reception and the perlocutionary effects of such political communication.